Comparative evaluation of UV/VIS and HPLC analytical methodologies applied for quantification of flavonoids from leaves of Bauhinia forficata - Marques,Graziella S. (2013)
Spectrophotometric determinations (direct dilution or after acid hydrolysis) of flavonoid content in leaves of Bauhinia forficata Link, Fabaceae, from two different regions from Brazil were compared with contents of kaempferitrin quantified by HPLC analysis. The absence of kaempferitrin peak in one sample denotes the risk of LC-method failure. On the other hand, the both spectrophotometric assays showed satisfactory performance and do not underwent influence from absence of kaempferitrin. Since several flavonoids are present in the herbal material, different content of flavonoids were observed for each analytical procedure. However, a strong positive association could be detected among methods (R²>0.99). Although a conversion factor should be adopted to compare procedures, the data showed that the spectrophotometric methods remain as an important tool for analysis of complex matrices such herbal drugs, notably when there aren't any pharmacological or chemical marker established for the species. Moreover, it's possible to suggest that the techniques studied in this work exhibit similar performance under the conditions employed. Nevertheless, before the adoption of kaempferitrin as an analytical marker by HPLC for Bauhinia species, the pharmacological knowledge should be better developed. In this cases, the use of spectrophotometric assay provide higher assurance of the reproducibility of the efficacy and safety.